Lower limit to Si-dimension for retaining graphenic carbon based 'buffer' effective towards bestowing Si-electrodes with cyclic stability. (15th September 2020) - Jangid, Manoj K.; Sonia, Farjana J.; Aslam, M.; Mukhopadhyay, Amartya
Abstract: The main avenue towards improving cyclic stability of Si-based anodes for Li-ion batteries has been the incorporation of graphene-based 'buffer' interlayer. In this context, we bring to the fore a concept concerning the existence of a lower limit to the dimensional scale of Si, below which the effectiveness of graphene-based interlayer towards improving cyclic stability of Si-based electrodes may cease. Our studies have indicated that the concerned effectiveness of graphene-based interlayer breaks down for Si-dimension ≤ ∼50 nm, because the, otherwise, relatively constraint free dilation/contraction (upon lithiation/delithiation) of Si at Si/graphene interface (unlike at Si/Cu interface) no longer remains unconstrained. Graphical abstract: Image 1